Possible interspecific origin of the B chromosome of Hypsiboas albopunctatus (Spix, 1824) (Anura, Hylidae), revealed by microdissection, chromosome painting, and reverse hybridisation - Gruber, Simone Lilian [UNESP]; Diniz, Débora; Sobrinho-Scudeler, Patrícia Elda [UNESP]; Foresti, Fausto [UNESP]; Haddad, Célio Fernando Baptista [UNESP]; Kasahara, Sanae [UNESP] (Pensoft Publishers, 2014)
The B chromosome in the hylid Hypsiboas albopunctatus (2n = 22 + B) is small, almost entirely composed of C-positive heterochromatin, and does not pair with any chromosome of the A complement. B probe, obtained by microdissection and DOP-PCR amplification, was used to search for homology between the B and regular chromosomes of H. albopunctatus and of the related species H. raniceps (Cope, 1862). Reverse hybridisation was also carried out in the investigation. The B probe exclusively painted the supernumerary, not hybridising any other chromosomes in H. albopunctatus, but all H. raniceps chromosomes showed small labelling signals. This result might be an indication that differences exist between the repetitive sequences of A and B chromosomes of H. albopunctatus, and that the chromosomes of H. raniceps and the heterochromatin of the B chromosome of H. albopunctatus are enriched with the same type of repetitive DNA. In meiotic preparations, the B labelled about 30% of scored spermatids, revealing a non-mendelian inheritance, and the painted B in micronucleus suggests that the supernumerary is eliminated from germ line cells. Although our results could suggest an interespecific origin of the B at first sight, further analysis on its repetitive sequences is still necessary. Nevertheless, the accumulation of repetitive sequences, detected in another species, even though closely related, remains an intriguing question. © Simone L. Gruber et al.
Keywords: FISH; GISH; Heterochromatin; Hylidae family; Repetitive DNA; Replication banding; Supernumerary chromosome